Detecting scapegoat effects in the relationship between exchange rates and macroeconomic fundamentals - Lorenzo Pozzi; Barbara Sadaba (Bank of Canada, 2017)
This paper presents a new testing method for the scapegoat model of exchange rates that aims to tighten the link between the theory on scapegoats and its empirical implementation. This new testing method consists of a number of steps. First, the exchange rate risk premium, the unobserved time-varying structural impact of the macro fundamentals on the exchange rate and the unobserved fundamental of the model are estimated. Next, the scapegoat terms in the model's exchange rate equation are estimated under the restrictions implied by these first-step estimates. The scapegoat terms consist of macro fundamentals, i.e., potential scapegoats, interacted with parameter expectations, where the latter are proxied using survey data. We use a Bayesian Gibbs sampling approach to estimate the different steps of the methodology for eight countries (five developed, three emerging) versus the US over the period 2002Q1-2014Q4. The macro fundamentals we consider are real GDP growth, the inflation rate, the long-run nominal interest rate and the current account to GDP ratio. We calculate the posterior probabilities that these macro fundamentals are scapegoats. For the inflation rate, these probabilities are considerably higher than the imposed prior probabilities of 0.5 in five out of eight countries (including the Anglo-Saxon economies). We find little evidence to suggest that the other macro fundamentals we consider are scapegoats.
Keywords: G15; C32; F31; 330; Exchange rates; Econometric and statistical methods; International financial markets